IMPLEMENTASI SERTIFIKASI HALAL AMPLANG WARJOK DI DESA KAUMAN KABUPATEN KETAPANG (Tinjauan Terhadap Undang Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal) - Irsyadul Ibard; Firdaus Achmad; Suhardiman Suhardiman (Al-Aqad, 2025)
This study analyzes the implementation of halal certification for Amplang Warjok products in Kauman Village, Ketapang, based on Law No. 33 of 2014 on Halal Product Assurance. It employs a qualitative approach with field research methods. Data were collected through interviews and documentation, using primary data from direct information provided by business owners and secondary data obtained from books, journals, theses, and related articles. Data analysis followed the interactive model of Miles and Huberman, including data collection, reduction, presentation, and conclusion drawing. The findings indicate: (1) Business owners have submitted halal certification applications to the Indonesian Ulema Council (MUI), accompanied by field surveys to verify raw materials and production facilities; (2) In accordance with Article 4 of Law No. 33/2014, all products circulated and traded in Indonesia must be halal-certified—prompting business operators to renew their certificates periodically to remain legally operational.